The following performance between particle and fluid medium inside hydrocyclone with double vortex finders - Yuekan Zhang; Junru Yang; Peikun Liu; Xinghua Yang (Functional Materials, 2016)
In this paper, we used numerical simulations to study the effect of size, density and concentration of particles on the relative motion between two phases in a cyclone separator with double vortex finders, which is different than a traditional separator that has only one overflow pipe.